AB0646 Identification of risk factors for recurrence in polymyalgia rheumatica. (12th June 2018) - Ueno, A.; Hirata, M.; Yamamura, Y.; Fujita, K.; Shibutou, N.; Yamamura, M.
Abstract : Background: Glucocorticoids (GCs) are effective for polymyalgia rheumatica (PMR); however, some patients relapse during GC tapering and develop adverse events of GCs. Objectives: To identify risk factors for recurrence in patients with polymyalgia Rheumatica(PMR). Methods: Cox proportional hazards regression analyses was performed 78 patients with PMR who had been treated by 2015 EULAR/ACR recommendations between January2015 and December 2017 in our centre. The following data at baseline were collected retrospectively: age, sex, time of diagnosis, location of arthralgia/myalgia, maximum dose of prednisolone, US findings of shoulder, laboratory data before the initial treatment. Results: Seventy-eight patients had been diagnosed with the 2012 EULAR/ACR provisional classification criteria for PMR, and had been treated first with GCs. They were at the age of 71.7±9.5, including 34 males and 44 females. Duration of symptoms before therapy was 2.0±2.0 months and the PMR duration was 21.2±15.5 months. Twenty-seven patients had arthralgia/myalgia other than shoulders and hips. The maximum dose of prednisolone was 15.9±4.4 mg/day. US findings of shoulder were positive in 65 patients. Relapses occurred in 37 patients (47%), when the dose of prednisolone was reduced to 5.6±5.5 mg/day at 8.9±6.4 months. MTX (8.6±3.1 mg/wk) was added in 29 patients or the dose of prednisolone was increased in 8 patients, similarly to the 2015 EULAR/ACR recommendations for the management of PMR. Additional MTX was ineffective in 16 patients, followed by adding tocilizumab in 8 patients. Forty patients discontinued GCs at 17.6±10.6 months. On univariate analysis, 4 variables were identified as significant risk factors affecting PMR recurrence: increased platelets (p=0.00192), low IgA (p=0.00149), arthralgia/myalgia limited to shoulders and hips (p=0.02), and the maximum dose of prednisolone used (p=0.0062). These 4 variables were introduced into the multivariate analysis, and the following 3 variables were retained as independent significant risk factors: the maximum dose of prednisolone(p<0.005), limitation of arthralgia/myalgia to shoulders and hips(p<0.05) and low IgA (p<0.005). Conclusions: These results indicate that the maximum dose of prednisolone, the absence of peripheral joint pains and low IgA may be associated with the recurrence in PMR patients Disclosure of Interest: None declared